Dinamic of water quality on maintenance jurung fish (Tor soro) that maintained on various recirculation systems - Fadir, Raja Muhammad; Haser, Teuku Fadlon; Febri, Suri Purnama; Prihadi, Tri Heru; Cahyanti, Wahyulia (Acta Aquatica: Aquatic Sciences Journal, 2022)
The recirculation system in the maintenance of tortoise will affect several water quality parameters, also known as water quality dynamics. Water quality such as temperature, DO, pH, turbidity, nitrate, nitrite, alkalinity, total hardness, TAN are parameters that are directly related to the physiological system of fish. The purpose of this study was to see the effect of various recirculation systems on water quality dynamics. This study used an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 3 replications and fish were kept for 20 days. The results obtained during the research include physical and chemical parameters. The temperature was between 24.5Co-27.6Co, the highest temperature measured in the current recirculation system treatment, the degree of acidity (pH) the average pH value ranged from 6.10-7.42. The value of nitrite ranged from 0.041-0.083 mg/L. Nitrate values ranged on average from 4.40 to 5.32. The average alkalinity value ranges from 44.02 to 77.30 alkalinity has a large effect on pH. Ammonia is produced from the excretory activity of fish, the average value of ammonia is 0.05 - 0.2 mg/L. In this study, the highest survival rate was found in the current recirculation treatment with a survival rate of 99%, and the lowest survival value was found in the non-recirculating treatment with a value of 53.5%. In this study, water quality is very influential on the survival of the jungle fish.Keywords: water quality; jurung fish; maintenance; recirculation; Dynamics system